2018
DOI: 10.1111/epi.14457
|View full text |Cite
|
Sign up to set email alerts
|

Effect of modified Atkins diet in adults with drug‐resistant focal epilepsy: A randomized clinical trial

Abstract: In this RCT investigating the effect of an adjunctive modified Atkins diet on seizure frequency in adults with difficult-to-treat focal epilepsy, we found a significant reduction in seizure frequency in the diet group compared to the controls, but only for moderate benefit (>25% seizure reduction) among those who completed the intervention. However, seizure response varied considerably between individuals, perhaps negatively influenced by a drop in serum concentrations of antiepileptic drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
78
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 24 publications
5
78
1
3
Order By: Relevance
“…The seizure frequency reductions in 5 of 11 participants treated with MCTs was encouraging, and, if confirmed, is comparable to other types of diets. Several studies with ketogenic diet or modified Atkin's diets have found similar antiseizure effects in children 14,15 and often adults 16 (although not consistently 17 ).…”
Section: Limitations Generalizability Interpretation Of Anti-seizmentioning
confidence: 95%
See 2 more Smart Citations
“…The seizure frequency reductions in 5 of 11 participants treated with MCTs was encouraging, and, if confirmed, is comparable to other types of diets. Several studies with ketogenic diet or modified Atkin's diets have found similar antiseizure effects in children 14,15 and often adults 16 (although not consistently 17 ).…”
Section: Limitations Generalizability Interpretation Of Anti-seizmentioning
confidence: 95%
“…6,7; Figure 1). 17). [8][9][10][11][12] This decreases the capacity for TCA cycle flux and subsequent ATP, amino acid, and lipid production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are in line with reports from meta-analyses of observational studies using MAD in adults [52]. The second RCT in Norway compared the change in seizure frequency following intervention in patients with drug-resistant (who had tried ≥3 AEDs) focal or multifocal epilepsy randomized to either 12 weeks of MAD (37 patients, of whom 28 received the intervention and 24 completed the study) or their habitual diet (38 patients, of whom 34 received the intervention and 32 completed the study) [59]. While they found no statistically significant difference in seizure frequency nor in 50% responder rate between the two groups following the intervention, a significant reduction in seizure frequency in the diet group compared to controls was observed among patients who completed the study but only for moderate benefit (25–50% seizure reduction).…”
Section: Kds In the Management Of Adult Epilepsy And Refractory Sementioning
confidence: 99%
“…While they found no statistically significant difference in seizure frequency nor in 50% responder rate between the two groups following the intervention, a significant reduction in seizure frequency in the diet group compared to controls was observed among patients who completed the study but only for moderate benefit (25–50% seizure reduction). Importantly, compared to the patient population in the Iranian RCT with roughly half generalized and focal epilepsy patients (length of epilepsy 14–17 years on average, 6–9 mean seizures per month and had tried on average 3–4 AEDs), the Norwegian study investigated MAD treatment in adults with solely focal epilepsy who were particularly drug-resistant (length of epilepsy more than 20 years on average, with a median of 15 seizures per month and had tried on average 9–10 AEDs) and did note an improvement in overall seizure severity in the diet group, as measured by the Liverpool Seizure Severity Scale [58,59]. Additional RCTs of larger sample size are warranted to investigate MAD efficacy in different subpopulations of adult epilepsy patients.…”
Section: Kds In the Management Of Adult Epilepsy And Refractory Sementioning
confidence: 99%